Study evaluating chronic abdominal pain and functional abdominal pain syndrome - Gupta, Sangeeta; Gupta, Gaurav; Sharda, Prateek; Mittal, Karan (International Journal of Research in Medical Sciences, 2017)
Background: Chronic abdominal pain (CAP) is a prevalent condition with a wide etiology and is often associated with significant health care utilization. A functional diagnosis, particularly, Functional abdominal pain syndrome (FAPS) is more challenging and has been a less extensively studied condition in adults as compared to other common functional gastrointestinal disorders. Hence, this study attempts to formulate a definite line of investigations, study various causes of chronic abdominal pain and to evaluate FAPS, in a population from Central India. Methods: 100 patients in the age-group of 10-60 years with chronic abdominal pain were selected. A careful history, clinical examination and investigations were performed and final diagnosis was made on the basis of the available data. Results: Eighty-nine out of hundred patients were found to be having some organic disorder causing CAP while eleven had functional gastrointestinal disorders. FAPS was diagnosed in three patients on the basis of Rome III diagnostic criteria while one had unspecified functional abdominal pain. Conclusions: CAP is a multifactorial condition yet, a thorough history coupled with a complete physical examination and investigative profile help to a great extent in diagnosing the cause. FAPS should be diagnosed on the basis of a careful clinical history and characteristic pain behaviour during physical examination. A cost-effective and conservative approach should be adopted for investigations. Unlike the organic causes, FAPS should be treated with a biopsychosocial approach with a variable combination of pharmacological, cognitive-behavioural and psychological interventions.